Peptide separation selectivity in proteomics LC‐MS experiments: Comparison of formic and mixed formic/heptafluorobutyric acids ion‐pairing modifiers. Issue 20 (9th September 2020) - Gussakovsky, Daniel; Anderson, Geoff; Spicer, Vic; Krokhin, Oleg V.
Abstract: Separation selectivity and detection sensitivity of reversed‐phase high‐performance liquid chromatography with tandem mass spectrometry analyses were compared for formic (0.1%) and formic/heptafluorobutyric (0.1%/0.005%) acid based eluents using a proteomic data set of ∼12 000 paired peptides. The addition of a small amount of hydrophobic heptafluorobutyric acid ion‐pairing modifier increased peptide retention by up to 10% acetonitrile depending on peptide charge, size, and hydrophobicity. Retention increase was greatest for peptides that were short, highly charged, and hydrophilic. There was an ∼3.75‐fold reduction in MS signal observed across the whole population of peptides following the addition of heptafluorobutyric acid. This resulted in ∼36% and ∼21% reduction of detected proteins and unique peptides for the whole cell lysate digests, respectively. We also confirmed that the separation selectivity of the formic/heptafluorobutyric acid system was very similar to the commonly used conditions of 0.1% trifluoroacetic acid, and developed a new version of the Sequence‐Specific Retention calculator model for the formic/heptafluorobutyric acid system showing the same ∼0.98 R 2 ‐value accuracy as the Sequence‐Specific Retention calculator formic acid model. In silico simulation of peptide distribution in separation space showed that the addition of 0.005% heptafluorobutyric acid to the 0.1% formic acid system increased potential proteome coverage by ∼11% of detectable species (tryptic peptides ≥ four amino acids).